Rancang Bangun Pembangkit Listrik Tenaga Mikro Hidro (PLTMH) - Roberto Sinaga Roberto; Indra Roza; Ahmad Yanie (JOURNAL OF ELECTRICAL AND SYSTEM CONTROL ENGINEERING, 2026)
This study aims to design and build a Micro Hydro Power Plant (PLTMH) as an alternative solution for providing electrical energy in remote areas with adequate water flow potential. PLTMH utilizes kinetic energy from river flow to drive a turbine, which is converted into electrical energy through a generator. The research process involves several important stages: survey of water flow potential, design of mechanical and electrical systems, and installation and testing of the system. The survey aims to determine the optimal water discharge, while the design includes the selection of components such as turbines, generators, and electrical power control systems. The results of the study indicate that the designed PLTMH is capable of producing 1 kW of electrical power, sufficient to meet the basic needs of several households in remote areas. Further testing indicates that this system operates with high efficiency, stability, and minimal environmental impact, making it an environmentally friendly technology. Other advantages are the stability of the electricity supply produced and ease of maintenance and operation. This PLTMH is a sustainable solution for limited access to electrical energy in rural areas. Given its wide application potential, PLTMH can contribute to reducing dependence on conventional electricity networks and providing an affordable and reliable energy alternative for communities in hard-to-reach areas.